Association of psychosocial factors with medication adherence in emerging adults with youth‐onset type 2 diabetes: The iCount study. Issue 8 (20th October 2022) - Trief, Paula M.; Kalichman, Seth; Uschner, Diane; Tung, Melinda; Drews, Kimberly L.; Anderson, Barbara J.; Fette, Lida M.; Wen, Hui; Bulger, Jane D.; Weinstock, Ruth S.
Abstract: Aims: To assess associations of psychosocial factors with medication adherence in young adults with youth‐onset type 2 diabetes in the Treatment Options for type 2 Diabetes in Adolescents and Youth (TODAY2) cohort. Methods: Participants (mean age 26 years) completed validated psychosocial measures. Adherence to oral hypoglycemia agents (OHAs) was assessed with 3‐monthly unannounced phone pill counts; insulin adherence by self‐report. Logistic and linear regressions identified factors associated with "low‐adherence" (<80% of pills/insulin) controlling for confounders. Results: Of 212 participants taking OHAs (67% female, 39% Hispanic, 36% non‐Hispanic Black), 69.8% were low‐adherent. After adjustment, beliefs that medicines are necessary was associated with lower odds of low‐adherence ( p = 0.040, dichotomous). Less self‐management support ( p = 0.008), no healthcare coverage ( p = 0.001), ≥1 ( p = 0.008)/≥2 ( p = 0.045) need insecurities were associated with higher odds of low‐adherence. Factors associated with lower % adherence (continuous) were beliefs that medicines are harmful ( p < 0.001)/overused ( p = 0.007)/less necessary ( p = 0.022), low self‐management support ( p = 0.003), food insecurity ( p = 0.036), no healthcare coverage ( p < 0.001), ≥1 ( p = 0.003)/≥2 ( p = 0.018) need insecurities. Of 192 taking insulin (69% female, 36% Hispanic, 41% non‐Hispanic Black, 16% non‐Hispanic white), 37.0% were low‐adherent. Beliefs that medicines are overused ( p = 0.009), that diabetes is not serious ( p = 0.010), low diabetes self‐efficacy ( p = 0.035), high distress (p = 0.027), low self‐management support ( p = 0.001), food insecurity ( p = 0.020), ≥1 ( p = 0.011)/≥2 ( p = 0.015) insecurities increased odds of insulin low‐adherence. Conclusions : Poor medication adherence, common in young adults with youth‐onset type 2 diabetes, is associated with interfering beliefs, diabetes distress and social factors. We must address these factors to develop tailored interventions for this vulnerable group.